Planos de texto e argumentatividade: dificuldades na produção e perspectivas para o ensino de textos dissertativo-argumentativos no Ensino Médio - Moraes, Jéssica de Almeida Fernandes (2025)
This dissertation, part of the research line on “Reading, Writing and Teaching on the Portuguese Language" of the Post-Graduate of the Portuguese Language Program from the Pontifical Catholic University of São Paulo focuses on on text plans and the construction of argumentativity. The study seeks to answer the following questions: (1) How are text plans, at macro and mesotextual levels, and argumentativity constructed in argumentative-essay texts produced by high school students? (2) What strategies involving text plans, textual sequences, and the development of argumentativity can be proposed to enhance high school students' proficiency in producing argumentative-essay texts? The general objective is to examine text plans and the construction of argumentativity in high school students' argumentative-essay texts. The specific objectives include: (1) identifying, describing, and analyzing text plans and the development of argumentativity in students' texts; (2) proposing strategies to facilitate the effective construction of argumentativity in argumentative-essay writing at the high school level. Grounded in the theoretical framework of text plans and their macro and mesotextual levels (Adam, 2011, 2019, 2021, 2022; Marquesi, 2017, 2021, 2022, 2023; Marquesi, Cabral & Rodrigues, 2020) and the prototype of argumentative sequences (Adam, 2011), this study draws on Textual Discourse Analysis. Additionally, it incorporates didactic sequences for text production (Dolz, Noverraz & Schneuwly, 2004; Zabala, 1998). A qualitative approach was adopted to enable a thorough analysis of the corpus, offering a comprehensive view of students' performance and deeper insights into the observed challenges. The findings reveal that high school students encounter significant difficulties in structuring text plans at macro and mesotextual levels, as well as in constructing effective argumentativity. However, the study demonstrates that, through the application of the analyzed theoretical concepts, it is possible to design strategies that enhance the teaching and learning of argumentative-essay writing. These strategies aim to address students' writing challenges, promoting progress in academic and professional contexts